Hedonic Shopping Motivation Terhadap Impulse Buying - Desianty Fithri Wahyuni; Indira Rachmawati (Jurnal Riset Bisnis dan Manajemen, 2018)
The purpose of this research is to know the perception of Telkom University student about hedonic shopping motivation and impulse buying at Tokopedia.This research is causal quantitative research. This research used non-probability sampling technique with purposive sampling to 385 respondents of Telkom University student and used an online survey. The results showed that hedonic shopping motivation and impulse buying were in the good criteria. Hedonic shopping has significant influence to impulse buying simultanously. Partially, there were positive significant influence from adventure/explore shopping, idea shopping, and relaxation shopping to impulse buying, while insignificant influences from value shopping and social shopping have negative significant effect.